El hispanismo alemán, la España contemporánea y Latinoamérica. Entrevista con el profesor Walther L. Bernecker / German Hispanism, Contemporary Spain and Latin-America: An interview with Professor Walther L. Bernecker - Pasamar, Gonzalo; Ceamanos, Roberto (Historiografías, 2017)
En esta entrevista el profesor Walther L. Bernecker desentraña aspectos fundamentales de la evolución del hispanismo y la historiografía alemanas. En sus respuestas, este afamado especialista germano ofrece pinceladas biográficas sobre su formación académica y sus multifacéticas inquietudes investigadoras. También ofrece una valoración sobre el estado del proceso de consolidación e internacionalización de la profesión histórica en España, la evolución política latinoamericana, así como sobre cuestiones relativas al debate entre la política, la historia y la memoria en la sociedad española, tales como la “Ley de Memoria Histórica” y la actual expansión del independentismo catalán. Palabras clave Hispanismo, Latinoamérica, profesionalización histórica, “Memoria Histórica”, “la cuestión catalana” Abstract In this interview, Professor Walther L. Bernecker reflects on fundamental aspects on the evolution of German Hispanism and historiography. In his answers, this well-known German expert offers biographical touches on his academic training and his many-sided interests in research. He also talks about topics such as the situation of process of internationalization of the Spanish historical profession, the evolution of politics in Latin-America, as well as issues concerning the debate on politics, history and memory in Spanish society, such as the Law of historical memory and the recent spread of Catalan independentism. Key Words Hispanism, Latin-America, historical professionalization, “historical memory”, “the Catalan question”